1985
DOI: 10.1071/ar9850443
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma-like organisms as causal agents of potato purple top wilt in Queensland

Abstract: The eggplant little-leaf agent was graft transmitted to tomato causing big-bud symptoms. Transmission from the big-bud tomato to potato by grafting or the leafhopper Orosius argentatus resulted in the development of purple top wilt symptoms. Thin-section electron microscopy revealed mycoplasma-like organisms present in the phloem sieve elements of a big-bud tomato plant and purple top wilt potato plants infected by grafting or leafhoppers. When tubers from graft-infected potato plants were planted, 73% produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Nagaich and Giri (1973) reported that purple top roll of potato in India was tuber transmitted to 6-33% of plants grown from tubers produced on infected plants. Similarly, Harding and Teakle (1985) reported tuber transmission rates of about 32% in purple top wiltaffected potatoes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nagaich and Giri (1973) reported that purple top roll of potato in India was tuber transmitted to 6-33% of plants grown from tubers produced on infected plants. Similarly, Harding and Teakle (1985) reported tuber transmission rates of about 32% in purple top wiltaffected potatoes.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, emerging phytoplasma diseases of potato (Solanum tuberosum L.) have increasingly become important in many potato producing areas around the world. In potatoes, diseases associated with phytoplasma infections include purple top, purple top wilt, potato witches'-broom, stolbur, aster yellows, and others (MacLeod 1954;Harding and Teakle 1985;Klein 2001;Wright 1952). Phytoplasmas in at least four different taxonomic groups have been identified on potatoes in Mexico (Santos-Cervantes et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, disease occurrence in beans and tobacco could be minimised by targeting herbicide applications to TbYDV host plants such as A. retroflexus and R. raphanistrum that were commonly found in and around crops at the two most disease-affected sites. Apart from TbYDV, O. orientalis also transmits phytoplasmas which cause a range of economically important phytoplasma-associated diseases in Australia such as legume little leaf (Hutton & Grylls, 1956), tomato big bud (Hill & Mandryk, 1954;Osmelak, 1986), lucerne witches broom (Helson, 1951), potato purple top wilt (Grylls, 1979;Harding & Teakle, 1985) and Australian lucerne yellows (Pilkington et al, 2004). Therefore, the results from this study will possibly lead to effective control strategies for not only TbYDV but also phytoplasma diseases vectored by O. orientalis.…”
Section: Discussionmentioning
confidence: 99%
“…On April 24, 2007, for each cultivar, 100 tubers were planted in 26-m 2 plots in a randomised complete block design with four replications. Twelve weeks after planting, all plants were visually inspected for symptoms of potato stolbur such as stunting, rolling or yellowing of upper leaflets, proliferation of axillary buds, formation of aerial tubers or swollen stems, cortical necrosis on lower stems, and sloughing of tissue and premature death (Harding and Teakle 1985;EPPO/CABI 1996). Three leaves of all symptomatic potato plants per replication from each cultivar were collected, stored in a cool box and subjected to PCR diagnosis using the primers fStol/rStol (Maixner et al 1995) to confirm stolbur phytoplasmal infections.…”
Section: Field Cultivar Screening Trialsmentioning
confidence: 99%